2010
DOI: 10.5194/hess-14-2343-2010
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for transboundary water resources planning and allocation: the case of Southern Africa

Abstract: Abstract. International water resources agreements for transboundary rivers in southern Africa are generally founded in system analysis models for water planning and allocation. The Water Resources Yield Model (WRYM) developed in South Africa has so far been the only model applied in official joint water resources studies aimed to form watersharing agreements. The continuous discussion around the model performance and growing distress over it being South African, where it was originally developed, while South … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…For models that allocate water across multiple time steps, links connect reservoir nodes in different time periods to represent carryover storage. These models have been applied in reservoir sizing (Kuczera, 1989;Khaliquzzaman and Chander, 1997), capacity expansion (Martin, 1987;Gondolfi et al, 1997), the derivation of reservoir operating rules (Lund and Ferreira, 1996;Bessler et al, 2003), water transfer during droughts (Cheng et al, 2009), and the optimal real-time flood control operation of reservoirs (Braga and Barbosa, 2001). Single time step models allocate water only within an operational unit period, but the allocation is sequentially solved in every step during the simulation time horizon.…”
Section: Framework Of a Network Flow Programming-based Allocation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For models that allocate water across multiple time steps, links connect reservoir nodes in different time periods to represent carryover storage. These models have been applied in reservoir sizing (Kuczera, 1989;Khaliquzzaman and Chander, 1997), capacity expansion (Martin, 1987;Gondolfi et al, 1997), the derivation of reservoir operating rules (Lund and Ferreira, 1996;Bessler et al, 2003), water transfer during droughts (Cheng et al, 2009), and the optimal real-time flood control operation of reservoirs (Braga and Barbosa, 2001). Single time step models allocate water only within an operational unit period, but the allocation is sequentially solved in every step during the simulation time horizon.…”
Section: Framework Of a Network Flow Programming-based Allocation Modelmentioning
confidence: 99%
“…The lack of a systematic and precise way to establish and interpret the objective function may prevent the model from being entrusted or accepted by all involved stakeholders. For example, Juízo and Lidén (2010) reported the experiences of implementing an optimization-based model on transboundary water allocation in South Africa. They found that "the results from the system analysis tool are not easily understood by the stakeholders, and government representatives of different countries bear some suspicion about the results".…”
Section: Introductionmentioning
confidence: 99%
“…These infrastructures, coupled with the need for improved operational skills of watershed-scale reservoirs and water distribution networks necessitates the development and application of water allocation models (Namchaiswadwong, 2004;Sert et al, 2007;Juízo and Lidén, 2010). Simulation-based allocation models are used to meet this need and they simulate water allocation with pre-determined water use priorities and reservoir operation rules.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation-based allocation models are used to meet this need and they simulate water allocation with pre-determined water use priorities and reservoir operation rules. These models have poor flexibility if anthropogenic and hydro-climatic factors are taken into consideration as they operate in a "what-if-then" scenario (Jha and Gupta, 2003). Therefore considering these limitations, integrated optimal water resources allocation modelling should consider all the water users and equitably allocate water amongst users, whilst taking into consideration hydro-climatic variability.…”
Section: Introductionmentioning
confidence: 99%
“…Scenario-based tools developed to support water management decisions, including HEC-5 (USACE, 1998), MIKE SHE (Graham and Butts, 2005), WEAP21 (Juizo and Liden, 2010) and WRAP (Wurbs, 2005), often have fixed demands, modelling environmental flows with flows for human needs, ignoring important differences between the two. Software for modelling river systems (e.g.…”
Section: Introductionmentioning
confidence: 99%